Sexually Transmitted Diseases A Practical Guide for Primary Care - Nelson, Anita L.; Woodward, Jo Ann (Current Clinical Practice, 2006)
Sexually Transmitted Diseases: A Practical Guide for Primary Care covers the diagnosis and treatment of STDs and other information critical to patient care in the new millennium. This collaboration provides the clinician with the ability to identify and manage Sexually Transmitted Infections (STIs), as well as obtain information about preventing their sequelae. Among the topics covered in this book are human papillomavirus and genital warts, genital herpes, viral hepatitis, HIV infection and AIDS, chlamydial and gonorrheal infections, and upper genital tract infections in women. Other topics of interest include syphilis, trichomoniasis, chancroid, granuloma inguinale, lymphogranuloma venereum, and molluscum contagiosum. Special consideration is given to ectoparasites, patient-clinician communication and STD care, cultural competence and STI care, effectiveness of barrier methods for STI prevention, and the future role of vaccines and microbides. Written by clinicians, many of whom have been diagnosing, treating, and counseling patents since the days of venereal disease, this book is packed with evidence-based information steeped in these clinicians' years of practice.